Double-blind, randomized, placebo-controlled crossover trial of alpha-lipoic acid for the treatment of fibromyalgia pain: the IMPALA trial. Issue 2 (February 2021) - Gilron, Ian; Robb, Sylvia; Tu, Dongsheng; Holden, Ronald; Towheed, Tanveer; Ziegler, Dan; Wang, Louie; Milev, Roumen; Gray, Christopher
Abstract : Abstract: Fibromyalgia is a common and challenging chronic pain disorder with few, if any, highly effective and well-tolerated treatments. Alpha-lipoic acid (ALA) is a nonsedating antioxidant with evidence of efficacy in the treatment of symptomatic diabetic neuropathy that has not been evaluated in the setting of fibromyalgia treatment. Thus, we conducted a single-centre, proof-of-concept, randomized, placebo-controlled, crossover trial of ALA for the treatment of fibromyalgia. Twenty-seven participants were recruited, and 24 participants completed both treatment periods of the trial. The median maximal tolerated dose of ALA in this trial was 1663 mg/day. Treatment-emergent adverse events with ALA were infrequent and not statistically different from placebo. For the primary outcome of pain intensity, and for several other validated secondary outcomes, there were no statistically significant differences between placebo and ALA. A post hoc exploratory subgroup analysis showed a significant interaction between gender and treatment with a significant favourable placebo–ALA difference in pain for men, but not for women. Overall, the results of this trial do not provide any evidence to suggest promise for ALA as an effective treatment for fibromyalgia, which is predominantly prevalent in women. This negative clinical trial represents an important step in a collective strategy to identify new, better tolerated and more effective treatments for fibromyalgia. Abstract : This double-blind, placebo-controlled proof-of-concept trial of alpha-lipoic acid for fibromyalgia pain was negative for the primary analysis. Exploratory analysis suggested possible benefits in men.